POLITIK HUKUM PENGATURAN PERLINDUNGAN PEKERJA RUMAH TANGGA DI INDONESIA DALAM PERSPEKTIF HAK ASASI MANUSIA - Eka Aninda Amaliyah; Rizqiyah Anabila, Hilyah (Journal of Law and Administrative Science, 2025)
Abstract. Domestic workers as informal workers require special attention and protection from formal workers. Domestic workers are classified as informal workers, so the Employment Law cannot be used to protect them. In this case, the protection provided is in the form of balancing the rights and responsibilities of Domestic Workers and employers, as well as ensuring safety so that Domestic Workers can obtain decent work. Indonesia is a country that prioritizes the protection of human rights by upholding the values ​​of human dignity and dignity as a whole. However, in Indonesia there are no comprehensive laws and regulations to protect local workers. Qualitative analysis was used to compile this study. This study is normative juridical, focusing on the study of the application of positive legal rules or norms. The results of the author's research show that domestic workers are considered vulnerable to various weaknesses in carrying out their duties. This shows the importance of protection for domestic workers. Therefore, the Law on the Protection of Domestic Workers provides protection for domestic workers while also providing protection for employers, especially in terms of ensuring a fair balance between the rights and responsibilities of both parties.